Laparoscopic mesh-augmented hiatoplasty without fundoplication as a method to treat large hiatal hernias - Linke, Georg R.; Gehrig, Tobias; Achtstätter, Lena Verena; Göhl, Anna Susanne; Kenngott, Hannes Götz; Schäfer, Fritz; Fischer, Lars; Gutt, Carsten N.; Müller, Beat P. (Surgery today, 2014)
Laparoscopic hiatal hernia repair with additional fundoplication is a commonly recommended standard surgical treatment for symptomatic large hiatal hernias with paraesophageal involvement (PEH). However, due to the risk of persistent side effects, this method remains controversial. Laparoscopic mesh-augmented hiatoplasty without fundoplication (LMAH), which combines hiatal repair and mesh reinforcement, might therefore be an alternative.